Model Komunikasi dalam Mitigasi Bencana Banjir di Kabupaten Kerinci dan Sungai Penuh - Nuzuli, Ahmad Khairul (Fakultas Ekonomi dan Ilmu Sosial Program Studi Ilmu Komunikasi Universitas AMIKOM Yogyakarta, 2024)
This article discusses the problems of development communication in flood disaster mitigation in Kerinci Regency and Sungai Penuh City. Kerinci Regency with its mountainous topography and extensive river network often experiences flood disasters, which have worsened in recent years. This study aims to explore an effective communication model in reducing the impact of flooding and improving community preparedness. Using a literature study method, this study highlights the importance of two-way communication between the government and the community, community-based education, and the use of modern technology such as social media and mobile applications. The results of the study indicate that a participatory communication model that actively involves the community and a technology-based early warning system can improve disaster mitigation and community response. This article provides a more inclusive communication approach, involving various stakeholders, to strengthen community resilience to future disasters.